Pengaruh sikap bahasa terhadap hasil belajar mata kuliah Bahasa Indonesia mahasiswa perguruan tinggi swasta Keuskupan Agung Ende - Age, Maria Yulita C. (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
Technological advances have influenced the mindset of Indonesian language users, affecting the way they use the language. This study examines the language attitudes of students at private universities in the Archdiocese of Ende and their impact on learning outcomes in Indonesian language courses. The the research integrates both qualitative and quantitative methodologies. A total of 300 respondents from three private universities in the Archdiocese of Ende were surveyed. Quantitative data obtained via a questionnaire were analysed using simple linear regression techniques with SPSS software, while qualitative responses gathered from guided interviews were processed through coding, synthesis, and inference. The results of the research show that students' positive attitudes towards language influence their performance in Indonesian language courses. Simple regression analysis showed a significance value of 0.00, which is less than 0.05, revealing a strong association between learners’ language perceptions and academic performance in Indonesia. Internal factors influencing students' language attitudes include proficiency in the language and motivation to use it, while external factors include social media influence. These results contribute to shaping teaching methods and Indonesian language policies in higher education.